Determination of IntegrinÎ±2 (ITGA2), Progesterone, Prolactin, Estradiol, Zinc and Vitamin C in Serum of Female Iraqi Patients with Breast Cancer - Al-Abassi, Hazima Mossa; Almohaidi, Asmaa M. Salih; Raheem ALMusawi, Amenah Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Back ground: Cancer is the second leading cause of death throughout the world. Breast cancer, is one of the leading mortality reasons in women from Western Countries, in Iraq, breast cancer is the second reason of death After cardiovascular Diseases.Material and method:The study was carried out of period from October/2016-january /2017 and  included (90) serum samples for Iraqi women suffered from breast cancer . Samples were divided into two groups ,the first group included (66) patients (females) their age rang (22-55) years which attended to (tumor unit) at medical city educational oncology hospital and Al-Amal Al-Waatanii hospital in Baghdad ,the second group included (38) for females apparently healthy their age (22-55) were studied as a control group. All patients women which included in this study were enrolled to a diagnostic criteria which made according to clinical, mamografical, histological finding. All of them were early diagnosed (without treatment).The disease was diagnosed by consultant medical staff at the hospital .Three (3ml) of peripheral blood has been drawn from both understudying groups, serum isolated and placed in Eppendorf tube in deep freeze (-20) until used. To determin the understudying  hormones (progesterone ,prolactin and estradiol ),Eliza technique has been used while  vitamin c and zinc were determined sepctrophotometricly.Result: By ELISA technique (ITGA2) recorded a non-significant differences in patients. Progesterone recorded a significantly increasing in patients (P